Dual-phase SilMA hydrogel: a dynamic scaffold for sequential drug release and enhanced spinal cord repair via neural differentiation and immunomodulation - Zhang, Ruizhi; Zhang, Mingzhe; Chen, Lu; Jiang, Linlin; Zou, Chenbo; Li, Na; Zhou, Hengxing; Feng, Shiqing (Frontiers in Bioengineering and Biotechnology, 2024)
Spinal cord injury (SCI) is a severe central nervous system disorder that leads to significant sensory, motor, and autonomic dysfunctions. Despite progress in surgical techniques and high-dose hormone therapies, clinical outcomes remain inadequate, underscoring the need for innovative therapeutic approaches. In this study, we developed a Dual-Phase Silk Fibroin Methacryloyl (SilMA) hydrogel scaffold (DPSH), incorporating PLGA microspheres encapsulating neurotrophin-3 (NT-3) and angiotensin (1-7) (Ang-(1-7)). This advanced scaffold is designed to provide a temporally controlled release of therapeutic agents, aimed at reducing inflammation during the acute phase of SCI and promoting neuronal differentiation and axonal regeneration in subsequent stages, thereby enhancing neural repair. Comprehensive characterization revealed that the DPSH possesses a highly porous architecture, appropriate mechanical properties for spinal cord tissue, and stability unaffected by the incorporation of microspheres and drugs. In vitro studies showed that Ang-(1-7) significantly induced M2 microglia polarization by [1.8-fold] (p < 0.0001), reducing inflammation, while NT-3 enhanced neural stem cell differentiation into neurons by [3.6-fold] (p < 0.0001). In vivo, the DPSH group exhibited significantly higher Basso Mouse Scale (BMS) scores (p < 0.0001), enhanced motor function, reduced astrocyte scarring by [54%] (p < 0.05), and improved neuronal survival and regeneration. These findings underscore the therapeutic potential of the DPSH scaffold for SCI repair, offering a novel strategy to enhance neural recovery by combining immunomodulation and neuroregeneration.